Answer:
<h2> a = 2, b = -1 </h2>
Step-by-step explanation:
p(x) = ax³ + x² - 2x + b
p(1) = a(1)³ + 1² - 2•1 + b = a + 1 - 2 + b = a + b - 1
a + b - 1 = 0 ⇒ b = 1 - a
p(-1) = a(-1)³ + (-1)² - 2(-1) + b = -a + 1 + 2 + b = - a + b + 3
- a + b + 3 = 0 ∧ b = 1 - a
- a + (1 - a) + 3 = 0
- a + 1 - a + 3 = 0
-2a + 4 = 0
-2a = -4
<u>a = 2</u>
<u>b = 1 - 2 = -1</u>
Answer:
347 people relating person male 3 given
It has an infinite rotation symmetry because no matter how you rotate the object, it look the same.
Answer:
10 - 3x
Step-by-step explanation:
Since the number 10 is decreased by 3x, that would mean the expression is 10 - 3x.
Hope this helped!
Answer:
x < 3
Step-by-step explanation: